2011
DOI: 10.1016/j.ygeno.2011.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the genome diversity of B. cereus and evolutionary aspects of B. anthracis emergence

Abstract: Here we report the use of a multi-genome DNA microarray to investigate the genome diversity of Bacillus cereus group members and elucidate the events associated with the emergence of B. anthracis the causative agent of anthrax–a lethal zoonotic disease. We initially performed directed genome sequencing of seven diverse B. cereus strains to identify novel sequences encoded in those genomes. The novel genes identified, combined with those publicly available, allowed the design of a “species” DNA microarray. Comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 93 publications
(144 reference statements)
1
26
0
Order By: Relevance
“…The great homogeneity of B. anthracis in the natural environment may be the result of the organism spending the majority of its life as a dormant spore (62). In this particular state, B. anthracis is not exposed to DNA-altering events such as the presence of phages and constant replication of DNA (59,61); this considerably limits the amount of genetic diversity found among isolates of this species (62) compared with B. cereus, which more commonly exists in the environment as vegetative cells (63). Regarding the markers highlighted in this study, ϳ5 distinct B. cereus proteoforms exist on average for a given protein versus a single B. anthracis proteoform (supplementary Table S6).…”
Section: Discussionmentioning
confidence: 99%
“…The great homogeneity of B. anthracis in the natural environment may be the result of the organism spending the majority of its life as a dormant spore (62). In this particular state, B. anthracis is not exposed to DNA-altering events such as the presence of phages and constant replication of DNA (59,61); this considerably limits the amount of genetic diversity found among isolates of this species (62) compared with B. cereus, which more commonly exists in the environment as vegetative cells (63). Regarding the markers highlighted in this study, ϳ5 distinct B. cereus proteoforms exist on average for a given protein versus a single B. anthracis proteoform (supplementary Table S6).…”
Section: Discussionmentioning
confidence: 99%
“…Phylogenetic studies have shown that the B. cereus group of species is actually a single species, although the nomenclature does not reflect this (61). B. cereus G9241 occurs earlier on a phylogenetic tree of the B. cereus group than B. anthracis (62), yet the genes involved in anthrax disease are carried by extrachromosomal plasmids, which play an important role in Bacillus diversity and allow for horizontal gene transfer.…”
Section: Discussionmentioning
confidence: 99%
“…The huge amount of genetic information from recent and ongoing Bacillus sequencing projects makes it feasible to design high-density whole genome microarrays to gain in-depth insights into genetic footprints of strains. For instance, Papazisi et al (2011) used a multi-genome DNA array to study the genomic diversity of B. cereus s.l. and evolutionary traits of B. anthracis .…”
Section: Third Generation Sequencing For Next Generation Diagnostics?mentioning
confidence: 99%